O możliwościach wykorzystania ultradźwięków w procesach zachodzących środowisku wodnym - Leśmian-Kordas, Ruta; Kąkolewski, Jan (Zielona Góra: Uniwersytet Zielonogórski)
The paper conteins a short review of contemporary achievements in sonochemistry and others processes developed under the influence of ultrasonie waves as well as the practical applications of ultrasonic field.
Keywords: ultradźwięki